2018
DOI: 10.1002/aelm.201800687
|View full text |Cite
|
Sign up to set email alerts
|

Improved Hole Injection into Perovskite Light‐Emitting Diodes Using A Black Phosphorus Interlayer

Abstract: The light‐output and efficiency of perovskite based light‐emitting diodes (PeLEDs) is limited by hole injection and high leakage current, generated by a high hole injection barrier and poor perovskite morphology, respectively. Here, a feasible strategy is reported to overcome both constraints by introducing 2D black phosphorus (BP) as hole injection layer in the PeLED stack. A continuous film composed of high‐quality, ultrathin, and large BP sheets on top of poly(3,4‐ethylenedioxythiophene) polystyrene sulfona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
(37 reference statements)
0
23
0
1
Order By: Relevance
“…Black phosphorous (BP), a new type of two‐dimensional (2D) material with high hole mobility, as a hole injection layer has been used in perovskite‐based light‐emitting diode (PeLED) and PSC devices to improve the hole extraction efficiency . Moreover, the recent theoretical studies had indicated that BP has an ideal function to retard charge recombination due to its unique self‐repairing properties .…”
mentioning
confidence: 99%
“…Black phosphorous (BP), a new type of two‐dimensional (2D) material with high hole mobility, as a hole injection layer has been used in perovskite‐based light‐emitting diode (PeLED) and PSC devices to improve the hole extraction efficiency . Moreover, the recent theoretical studies had indicated that BP has an ideal function to retard charge recombination due to its unique self‐repairing properties .…”
mentioning
confidence: 99%
“…Ricciardulli et al suggested a 2D black phosphorus (BP)/ organic PEDOT:PSS combined HTL with high charge carrier mobility for green-emitting PeLEDs. [149] Large and ultrathin BP flakes were synthesized by electrochemical exfoliation of bulk BP. When ultrathin and laterally large BP flakes were mounted on top of PEDOT:PSS, the deep HOMO (−5.32 eV) of thin-layered BP lowered the hole injection barrier between PEDOT:PSS and CsPbBr 3 .…”
Section: Organic/inorganic Hybrid Type Ctlsmentioning
confidence: 99%
“…Among them, 2D black phosphorous (BP) has been widely adopted to organic and MHP solar cells, attaining enhanced power conversion efficiencies owing to its high carrier mobility and deep HOMO level of −5.32 eV. [ 62 ] Exfoliated BP flakes formed large and ultrathin film, which contributes to smooth, uniform and continuous film on PEDOT:PSS. The BP layer decreased the injection barrier and assisted uniform MHP growth, therefore BP layer had a beneficial impact on increasing EQE.…”
Section: Hil and Htl Engineeringmentioning
confidence: 99%